IMPLIKASI CORPORATE SOCIAL RESPONSIBILITY TERHADAP KEPUASAN PELANGGAN PADA PT PELABUHAN INDONESIA II - Wibawanti, Andjar Budi; Untung, Sri; Pahala, Yosi (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2017)
This research is to find out the influence of corporate social responsibility (CSR) towards corporate image and its implication on customer satisfaction of PT Pelabuhan Indonesia II (Persero). The research method is using survey. The population is taken from customer of PT Pelabuhan Indonesia II (Persero) and with its sample of 100 customers taken by quota sampling. Data analysis used descriptive statistics and inferential statistics of path analysis. The result of the research shows that corporate social responsibility has positive and significant effect on customer satisfaction with indication of path coefficient = 0.45 and tct = 5.40> ttable (2,364). The conclusion of the research is corporate social responsibility influences customer satisfaction with the mediation of corporate image, hopefully customer satisfaction can be improved through improvement of CSR andcorporate image.